Innovation of Multimodal Digital Modules Based on Ethnomathematical Problems for Meaningful Mathematics Learning in Merdeka Curriculum - Suryawan, I Putu Pasek; Lasmawan, I Wayan; Suharta, I Gusti Putu (Journal of Education Reseach and Evaluation, 2023)
The essence of the curriculum Merdeka expects mathematics learning to be meaningful and in accordance with learning styles and needs.  Culture and technology are the right combination to be applied in mathematics learning to implement the curriculum Merdeka.  This research aims to develop multimodal digital modules based on ethno mathematical problems for meaningful mathematics learning that can adapt to technological developments. The development model used in this study is the ADDIE model. The service of the module is determined by the results of expert validation, practicality tests, and effectiveness tests by lecturers, teachers and students as research subjects. Based on the material validity test, a validity of 4.45 was obtained and a media validity test obtained a validity of 4.87 which was included in the Very High category. The average practicality score is 4.3 with very high criteria.  The range of grades obtained by students is 83%. Thus the modules developed can be said to be effective and feasible to use. Through the innovation of this module, learning becomes meaningful, accommodates every learning style and student need, and facilitates students to learn independently.